2020
DOI: 10.1002/mds.28366
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Dopamine Deficit and Motor Impairment in Idiopathic Normal Pressure Hydrocephalus

Abstract: Background Idiopathic normal pressure hydrocephalus can present with parkinsonism. However, abnormalities of the striatal dopamine reuptake transporter are unclear. Objectives To explore presence and features of striatal dopaminergic deficit in subjects with idiopathic normal pressure hydrocephalus as compared to Parkinson's disease (PD) patients and healthy controls. Methods We investigated 50 subjects with idiopathic normal pressure hydrocephalus, 25 with PD, and 40 healthy controls. All participants underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 44 publications
0
37
0
2
Order By: Relevance
“…This previous study has included a small number of iNPH in the group without parkinsonism. Recent studies have revealed that DAT availability decreases from 30.8-62.0% in patients with iNPH [12,13,14]. In other words, the results of discrimination in their study may vary depending on the proportion of iNPH with and without the pathophysiology of DAT reduction, if a large number of iNPH subjects were included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This previous study has included a small number of iNPH in the group without parkinsonism. Recent studies have revealed that DAT availability decreases from 30.8-62.0% in patients with iNPH [12,13,14]. In other words, the results of discrimination in their study may vary depending on the proportion of iNPH with and without the pathophysiology of DAT reduction, if a large number of iNPH subjects were included.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings suggest that CSF area mask correction might affect the visual and quantitative assessment of iNPH. The pathophysiology of DAT reduction, which was observed in approximately 30-60% of iNPH, has not been clari ed [12,13,14]. Therefore, future studies of DAT availability in iNPH require more accurate visual and quantitative analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by definition, iNPH shows no abnormalities on these tests. Nonetheless, as is the case with AD, comorbidity of PD and iNPH is not uncommon ( 58 ), and even the confirmation of DESH findings cannot rule out comorbid PD ( 59 ). If comorbidity is suspected, carefully determining the extent of iNPH involvement in the present symptoms using the response to a tap test and observing the reaction to dopamine replacement therapy for PD (L-dopa test) can aid diagnosis ( 60 ).…”
Section: Diagnosis With Csf Biomarkersmentioning
confidence: 99%
“…Auch bei einigen Patienten mit NPH findet sich ein reduzierter striataler Dopaminstoffwechsel. Ein unterstützender dopaminerger Therapieversuch erweist sich in diesem Krankheitsbild trotzdem nur in sehr seltenen Fällen als hilfreich, zumal hier durch die Shuntoperation und in Form von antidementiven Medikamenten alternative Optionen bestehen [13].…”
Section: Pharmakotherapie (Literaturübersicht In [10])unclassified